The correspondence of Ferdinand von Mueller: from nineteenth century paper to twenty first century data - McCarthy, Gavan (Circumscribere International Journal for the History of Science, 2018)
This paper presents a case study that demonstrates how a long term research activity, with the intention to create a scholarly edition of scientific correspondence, can be liberated from its print paradigm strictures to join the twenty first century world of interconnected knowledge. The Von Mueller Correspondence Project has produced a corpus of over 15,600 digitally transcribed letters and related materials focused on the period 1840 to 1896. These are complemented by materials in a range of forms that refer to Mueller dating from 1814 to 1931. Mueller was a prolific correspondent and established links with hundreds of fellow botanists and biologists across the globe; most of these, and certainly the most notable, will be registered in the History of Science Society Isis Cumulative Bibliography as Authority Records with links to publications about them and is some cases publications by them. The long-term plan is to systemically interlink the Von Mueller Correspondence Project digital corpus and the Isis Cumulative Bibliography and develop the synergies that will drive digital humanities analysis and future scholarly endeavour. That is the vision but what is the reality? At what stage is the project now? How did it get this far? What steps remain? How does the story of this project help us better understand the imperatives of digital scholarship – its strengths and its challenges?